Risk of occult gastrointestinal bleeding with increased gut Enterococcus and Staphylococcus for poor outcomes in ischemic stroke patients - Xia, Geng-Hong; Song, Wei; Xie, Jia-Hui; Liang, Jing-Ru; Yin, Jia (Frontiers in Neuroscience, 2025)
BackgroundGastrointestinal disorders are common in acute ischemic stroke (AIS) patients, but the impact of occult gastrointestinal bleeding (occult GIB) and its link to gut dysbiosis remain underexplored. Occult GIB, often undetected due to subtle symptoms, may significantly affect stroke recovery and long-term outcomes.MethodWe conducted a prospective, multi-center cohort study involving 482 AIS patients. Fecal samples collected within 48 h of admission were analyzed using 16S rRNA gene sequencing. Patients were followed for 1 year to assess major adverse cardiovascular events (MACEs), including death and recurrent stroke.ResultsOccult GIB was identified in 13.9% of patients, who had significantly higher rates of 90-day dependency (56.7% vs. 20.5%) and 1-year MACEs (28.6% vs. 15.5%) compared to non-GIB patients. These patients also exhibited higher infection rates and enrichment of specific gut pathogens, including Enterococcus, Staphylococcus, and Pseudomonas (all p < 0.05). Multivariate analysis revealed that elevated levels of these pathogens were independent risk factors for occult GIB. Furthermore, occult GIB independently predicted 90-day dependency (aOR 2.478, 95% CI [1.159–5.296]) and 1-year MACEs (aOR 1.905, 95% CI [1.003–3.617]).ConclusionOccult GIB is prevalent in AIS patients and is associated with worse long-term outcomes, particularly in those with enrichment of these specific gut pathogens. Early detection and management of occult GIB may improve patient outcomes. Future research should focus on elucidating underlying mechanisms and developing targeted interventions.